2011
DOI: 10.1159/000324134
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes and Late-Onset Alzheimer’s Disease

Abstract: Background/Aims: To confirm in a cohort recruited in 1999–2001 our finding in a cohort recruited in 1992–1994 relating type 2 diabetes (T2D) to late-onset Alzheimer’s disease (LOAD). Methods: Participants were 1,488 persons aged 65 years and older without dementia at baseline from New York City. T2D was ascertained by self-report. Dementia and LOAD were ascertained by standard research procedures. Proportional hazard regression was used for analyses relating T2D and LOAD. Results: The prevalence of T2D was 17%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 101 publications
3
76
1
8
Order By: Relevance
“…In 1999, the Rotterdam study reported that T2DM could double the risk of AD [39]. More recently, T2DM was shown to be associated with a 60% increase of AD risk [83]. The association between T2DM and AD was not observed in one study with very old T2DM subjects (≥80 years old) (48).…”
Section: T2dm As a Risk Factor For Admentioning
confidence: 99%
“…In 1999, the Rotterdam study reported that T2DM could double the risk of AD [39]. More recently, T2DM was shown to be associated with a 60% increase of AD risk [83]. The association between T2DM and AD was not observed in one study with very old T2DM subjects (≥80 years old) (48).…”
Section: T2dm As a Risk Factor For Admentioning
confidence: 99%
“…As neither of these risk factors is sufficient to trigger the pathogenesis of AD, it is reasonable to believe that a combination of a number of them determines whether or not an individual will suffer from the disease, as well as the age of onset. A wide variety of risk factors for AD have been investigated; although some results remain controversial, several studies show a relation between medical conditions such as hypertension, type 2 diabetes mellitus and high cholesterol and triglycerides blood levels, and the risk to develop late-onset AD (Irizarry 2004, Lane and Farlow 2005, Razay et al 2007, Cheng et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Associação positiva foi relatada entre DM e demência, DA e DV (Ott et al, 1996;Bowirrat et al, 2002). Nielson et al (1996) Onze estudos fizeram o diagnóstico de DM por autorrelato e/ou uso de medicamentos e/ou por histórico médico (Katzman et al, 1989;Brayne et al, 1998;Luchsinger et al, 2001;Hassing et al, 2002;Arvanitakis et al, 2004;Luchsinger et al, 2005;Borenstein et al, 2005;Hayden et al, 2006;Ahtiluoto et al, 2010;Cheng et al, 2011;Wang et al, 2012). Apenas dois estudos utilizaram a dosagem específica de glicemia jejum para o diagnóstico de DM (Irie et al, 2008;Kimm et al, 2011).…”
Section: Estudos Transversais E Retrospectivos Sobre Associação De Dmunclassified
“…A maioria desses estudos epidemiológicos mostrou uma associação positiva de DM com DA (Leibson et al, 1997;Brayne et al, 1998;Ott et al, 1999;Peila et al, 2002;Arvanitakis et al, 2004;Luchsinger et al, 2005;Borenstein et al, 2005;Ahtiluoto et al, 2010;Kimm et al, 2011;Cheng et al, 2011;Ohara et al, 2011;Wang et al, 2012). Entretanto, outros trabalhos descreveram nenhuma associação entre DM e DA, porém positiva para DM e DV (Curb et al, 1999;Luchsinger et al, 2001;MacKnight et al, 2002;Hassing et al, 2002;Raffaitin et al, 2009; (Leibson et al, 1997;Brayne et al, 1998;Arvanitakis et al, 2004;Luchsinger et al, 2005;Irie et al, 2008;Cheng et al, 2011;Wang et al, 2012).…”
Section: Estudos Transversais E Retrospectivos Sobre Associação De Dmunclassified
See 1 more Smart Citation